2003
DOI: 10.1021/jp035246f
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cytochrome C on New Mesoporous Carbon Molecular Sieves

Abstract: Carbon mesoporous molecular sieves have been prepared from SBA-15 materials synthesized at different temperatures. This allows the synthesis of hexagonally arranged mesoporous carbons with pore diameters between 3.0 nm (CMK-3-100) and 6.5 nm (CMK-3-150). The novel materials have been studied in the adsorption of horse heart cytochrome c from solutions with different pH. A maximal adsorption capacity of 18.5 µmol/g was found for CMK-3-130 (d p ) 4.5 nm) at pH 9.6, which is near the isoelectric point of cytochro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
180
1
5

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 243 publications
(188 citation statements)
references
References 17 publications
2
180
1
5
Order By: Relevance
“…For adsorption isotherm measurements, pH ¼ 9.6 (near the pI of cyt c) and pH ¼ 4.8 (near the pI of BSA) were chosen because the adsorption capacity can be maximized near the pI. [23,54,55,56] The experimental adsorption isotherms of cyt c and BSA on MSNs-C 18 -2 at 30 8C and both pH values as well as their fitting curves by Langmuir equation are shown in Figure 9. All isotherms show a sharp initial rise and then reach maximum adsorption amounts (plateau), suggesting that isotherms are of Langmuir type.…”
Section: Bioadsorption Isotherms and Binary Bioseparationmentioning
confidence: 99%
“…For adsorption isotherm measurements, pH ¼ 9.6 (near the pI of cyt c) and pH ¼ 4.8 (near the pI of BSA) were chosen because the adsorption capacity can be maximized near the pI. [23,54,55,56] The experimental adsorption isotherms of cyt c and BSA on MSNs-C 18 -2 at 30 8C and both pH values as well as their fitting curves by Langmuir equation are shown in Figure 9. All isotherms show a sharp initial rise and then reach maximum adsorption amounts (plateau), suggesting that isotherms are of Langmuir type.…”
Section: Bioadsorption Isotherms and Binary Bioseparationmentioning
confidence: 99%
“…3A(b)). Recently, Vinu et al reported successful tuning of SBA-15 structure upon control of synthetic temperature [95] and applied the pore-tuned SBA-15 replica to synthesize CMK-3 mesoporous carbon materials with pore diameter ranging from 3 to 6.5 nm [96].…”
Section: Carbon Nanocage and Mesoporous Carbon Nitride Via Replica Symentioning
confidence: 99%
“…Adsorption of proteins to mesoporous materials, especially to mesoporous silica, has been rapidly paid attentions [169][170][171][172][173][174][175][176][177][178][179][180][181][182][183][184][185]. As shown below, Vinu et al provide systematic researches on protein adsorption onto mesoporous materials [96,[186][187][188][189][190][191][192][193][194][195][196]. Typical results of adsorption of hen egg white lysozyme and horse heart cytochrome c are shown in Fig.…”
Section: Biomaterial-hybridized Mesoporous Materialsmentioning
confidence: 99%
“…Графитовые УНО образуют трехмерную пеноподобную структуру с большой удельной площадью поверхности. Таким обра-зом, УНО наиболее предпочтительны для применения в доставке лекарственных препаратов [6][7][8], разделении газов [9], в топливных элементах [10][11][12] и для очистки воды [13]. Наиболее перспективно применение УНО в качестве материала для изготовления электродов в суперконденсаторах и литий-ионных батареях высокой емкости, которые демонстрируют стабильность характе-ристик при многократной перезарядке [14][15][16][17][18].…”
Section: Introductionunclassified